UK and Australian University Students’ Perceptions of the Nature of Sexual Assault and Intervening Behavior - Labhardt, Danielle (Journal of interpersonal violence, 2024)
Sexual assault is a global problem, with the risk highest among university students. Bystander intervention preventing sexual assaults has primarily been researched using quantitative methods to understand what factors influence it. However, both sexual assault and bystander intervention are complex with many subtle and overlapping issues that, when analyzed qualitatively, can offer new insights. The current study aimed to explore and develop a nuanced and comprehensive understanding of students’ perceptions of sexual assault and bystander intervention across two universities, one in the United Kingdom and one in Australia. Thirty-nine university students (19 in the United Kingdom; 20 in Australia) took part in one-to-one semistructured interviews. Using inductive thematic analysis, two overarching themes were identified: (a) navigating the complex dynamics of sexual assault; and (b) decisions to intervene or not to intervene. Findings suggest that the complexity and ambiguity around sexual assault can forestall bystander intervention. As such, increasing education, awareness, and discussions around sexual assault and bystander intervention is vital to increase awareness of the problem and mobilize action from bystanders to prevent sexual assault.